MicroRNA‐339, an epigenetic modulating target is involved in human gastric carcinogenesis through targeting NOVA1. Issue 20 (29th September 2015) - Shen, Bo; Zhang, Yan; Yu, Shaorong; Yuan, Yuan; Zhong, Yuejiao; Lu, Jianwei; Feng, Jifeng
Abstract : The role of miR‐339 in human gastric cancer (GC) remains unclear. Here, we found that miR‐339 is remarkably decreased in primary GC tissues. Overexpression of miR‐339 in GC cells significantly suppressed proliferation, migration, invasion, and tumorigenicity. Furthermore, NOVA1 was confirmed as a target of miR‐339. Restoration of NOVA1 in miR‐339‐overexpressing GC cells partially impaired the inhibitory effects of miR‐339. More importantly, epigenetic modification may be involved in the modulation of miR‐339 expression. These findings uncover a novel role for miR‐339 in gastric carcinogenesis, and restoration of miR‐339 could be considered as a potential therapeutic strategy for GC treatment. Abstract : miR‐339 is significantly reduced in gastric cancer cells and tissues. miR‐339 inhibits cell proliferation, migration, invasion, and tumorigenicity. NOVA1 is a direct target of miR‐339. NOVA1 impairs the suppressive effects of miR‐339 on gastric cancer cells.